The phenomenon of the New Right in European and Latin American narrative literature: A Workshop’s Report - Palomar Vidal, Richard (apropos [Perspektiven auf die Romania], 2023)
The workshop “The phenomenon of the New Right in European and Latin American narrative literature: New perpetrators – old patterns of thinking?” organised by Dr. Lena Seauve took place on 13 October 2023 at the Institute for Latin American Studies (Lateinamerika-Institut) of the Freie Universität Berlin (Boltzmannstraße 1, 14195 Berlin). Far-right ideology has transcended national boundaries and now holds a global presence. This perspective served as the focal point for the workshop, providing a basis to examine the movement on a global scale. The workshop aimed to showcase this diverse phenomenon, connecting perspectives from European nations like France, Italy, and the United Kingdom, as well as South American countries, including Brazil, Argentina, and Chile. Its goal was to highlight commonalities among these nations and their literary landscapes, exploring figures, texts, and modes of thought related to the far-right ideology.